(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Migraine is one among the foremost prevalent and disabling disorders, characterized by recurrent headache attacks with nausea, vomiting, photophobia, and phonophobia. Nerivio Migra may be a breakthrough device for acute treatment of migraines. Attached to the patient’s arm (below the shoulder), it’s a clinically-tested wearable suited to be worn everywhere and at any time. Non steroidal anti inflammatory drugs (NSAIDs) and triptans, commonly used for acute migraine treatment3, may be ineffective, poorly tolerated, contraindicated, and if used in excess, may lead to medication overuse headache there is a great unmet need for alternative acute migraine treatments that are both effective and well tolerated. Non-invasive neuromodulation is safe, well tolerated, and may have fewer adverse effects than drugs. Remote electrical neuromodulation (REN) may be a novel acute migraine treatment that stimulates upper arm peripheral nerves to induce conditioned pain modulation (CPM)-an endogenous analgesia mechanism during which conditioning stimulation inhibits pain in remote body regions.